The Role of Parents and Buddhist Religious Education Teachers in Strengthening Student Character at Metta Maitreya Vocational School, Pekanbaru - Sudiani Sudiani; Mettadewi Wong; Situ Asih (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study is motivated by the importance of synergy between parents and Buddhist Religious Education teachers in strengthening student character, particularly in shaping learners who are not only academically competent but also morally grounded. The main issue addressed in this research is the suboptimal role of both parents and teachers in accompanying the character-building process of students, as well as challenges in internalizing Buddhist values into students’ daily lives at SMK Metta Maitreya Pekanbaru. The objective of this study is to analyze the roles of parents and Buddhist Education teachers in character development, identify inhibiting factors, and propose strategies for character strengthening based on compassion values. The study employs a descriptive qualitative approach through in-depth interviews, observation, and documentation. The results indicate that parents significantly contribute to building foundational character values through role modeling, communication, and supervision. Meanwhile, Buddhist Religious Education teachers act as spiritual mentors and exemplars of Buddhist virtues, integrating values into teaching and behavior. Challenges found include limited parent-child interaction time and the continued focus on cognitive learning aspects. This research proposes a character education approach rooted in the “Culture of Compassion,” composed of three core elements: a heart of compassion, acts of compassion, and smiles of compassion. This integrative approach is expected to reinforce students' internalization of noble values comprehensively. The conclusion emphasizes that collaboration between parents and teachers is essential for holistic and sustainable student character development.